Genetic counseling through a personalized bioethics perspective - Gajardo Ugás, Alejandra (Acta Bioethica, 2007)
Diseases of genetic origin presently cause around 34% of the deaths of minors under a year old. The knowledge obtained since the Human Genome Project begun has provided tools for prevention and cure. Among them genetic counseling is included, which must provide the basis for an informed decision over child gestation. These new technologies imply more and more usual and complex ethical issues. What to do with the information obtained? May it be used to cure genetic diseases? How to promote and assure this information’s ethical practice? The basis for genetic counseling and its ethical implications are presented here under a personalized perspective.